BS40 Hypoxia induces gene-specific epigenetic modifications in human cardiac fibroblasts. (May 2019) - Russell-Hallinan, Adam; Glezeva, Nadezhda; Moran, Bruce; Das, Sudipto; Baugh, John; Watson, Chris
Abstract : Introduction: Ischemia caused by coronary artery disease and myocardial infarction leads to aberrant ventricular remodelling and cardiac fibrosis. This occurs partly through accumulation of gene expression changes in resident fibroblasts, resulting in an overactive fibrotic phenotype. We have recently shown that human myocardial tissue hypoxia is associated with an enhanced pro-fibrotic gene profile in the tissue and, more significantly, that hypoxia-induced pro-fibrotic changes in cardiac fibroblasts are associated with global DNA hypermethylation. Purpose: Based on this epigenetics data, we have conducted a gene-specific methylation study to investigate methylation changes that occur in hypoxic ventricular fibroblasts and to gain novel insights into mechanisms that may contribute to post-ischemic cardiac remodelling. Methods: Human ventricular cardiac fibroblasts were exposed to 1% oxygen for up to 8 days. Global methylation changes were assessed using anti-5-methylcytosine (5MeC) staining, flow cytometry, QPCR, and western blot. Gene-specific methylation changes associated with hypoxia and an increased fibrotic state were determined by 5MeC immunoprecipitation and GeneChip human promoter arrays (Affymetrix), and validated by bisulphite genomic sequencing (BGS). Results: Hypoxia-induced pro-fibrotic changes in cardiac fibroblasts included increased cell proliferation and increased alpha smooth muscle actin, collagen 1, DNMT1 and DNMT3B expression which associated with global DNA hypermethylation. Array analysis revealed 37 gene-specific hypermethylation changes and 133-hypomethylation changes occurred in response to chronic hypoxia. Conclusion: Epigenetic modifications and changes in the epigenetic machinery identified in cardiac fibroblasts during prolonged hypoxia may contribute to the pro-fibrotic nature of the ischemic milieu in the heart during disease. The application of epigenetic-based therapy, such as DNA methylation modifiers, as a treatment option for cardiac pathologies associated with fibrosis and ischemia may provide therapeutic benefit. Conflict of interest: None